Haemosporidian blood parasites of passerine birds in north-western Siberia - Yusupova, Dina A.; Schumm, Yvonne R.; Sokolov, Aleksandr A.; Quillfeldt, Petra (2024)
Host–parasite interactions include effects on both proximate and ultimate levels: parasite infections affect individual’s fitness and play a significant role in shaping the life history of host species. Global environmental changes as well as significant shifts in abiotic factors might impact the dynamics of parasite–host interactions, especially in Arctic regions, where the climate is changing at an alarming rate. With global warming, parasites and their vectors are predicted to spread to polar latitudes, and it is crucial to follow the changes occurring in the ecosystems in the era of global changes. We studied blood parasites (Haemosporidae) of passerine birds (Passeriformes: Aves) in southwest Yamal (north-western Siberia) using genetic and morphological methods. We found an overall parasite prevalence of 76.3%, with highest values for Leucocytozoon (72.0%) and lower values for Parahaemoproteus and Plasmodium (8.9 and 8.2%, respectively). We determined 26 genetic lineages in total, five of them were novel. The most common parasite lineages were TRPIP2 (18%), BT1 (14%), novel ACAFLA06 (13%), BT2 (7%), novel ACAFLA07 (6%), BT4 (5%) for Leucocytozoon; SISKIN1 (4%) for Parahaemoproteus; TURDUS1 (4%) for Plasmodium. For redpoll (Acanthis flammea), brambling (Fringilla montifringilla), bluethroat (Luscinia svecica) and little bunting (Emberiza pusilla) overall prevalence exceeded 90%. We also found significant differences in prevalence and lineage composition between sample sites, species and sexes, and a positive correlation between number of infections and host body mass. Our study provides knowledge about haemosporidian infections in the region, which had been barely studied for blood parasites. Gathered information is essential for the future monitoring and assessing potential shifts due to global change.